KNOWLEDGE-BASED ECONOMY AND INNOVATIVE DEVELOPMENT - N. M. Abdikeev (Финансы: теория и практика, 2017)
The contemporary socio-economic and scientific-technological development is characterized by globalization, integration of economies, rapid movement of goods, services, people, capital and ideas. The transition to the sixth techno-economic paradigm is now in progress. Given that the techno-economic paradigm is represented by mastered breakthrough technologies, innovations and inventions, the development of scientific and technical progress, the cognitive and creative human component of technological processes along with the intellectualization of the main production factors are becoming the determining development factors.The knowledge-based economy is the one that creates, disseminates, and makes use of knowledge to ensure economic growth and competitiveness. This is an economy in which knowledge enriches all industries, all sectors and all participants of the economic processes. The main effect of the knowledge-based economy is its widespread utilization by all industries and sectors rather than just high-tech product manufacturing. Important in the knowledge-based economy is not so much creation of new knowledge as efficient application of the latter. The innovative development strategy of the country is based on realization of the human potential, more effective application of knowledge and skills of people to continuously improve the technology, economic performance and life of society as a whole. The transition to the innovative way of development is characterized primarily by investment in the human capital. Product, process and strategy innovations are objects of innovative management. Priority management segments are being developed in the search of additional sources to increase the profitability of companies ranging from financial and customer relations management to quality and knowledge management. The creative potential of employees increasingly ensures the competitive edge of a company. The paper addresses current aspects of the knowledge-based economy development, organizational and managerial innovation, the relationship between generation of innovations and effective knowledge management in a company as well as problems of producing innovators — leaders of changes in the innovation economy.